2013
DOI: 10.1111/aos.12217
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between visual acuity and interface reflectivity measured by pentacam following DSAEK

Abstract: . Purpose:  Descemet‐stripping automated endothelial keratoplasty (DSAEK) is an advanced method of lamellar endothelial keratoplasty. In comparison with penetrating keratoplasty, visual rehabilitation seems to be faster. Final visual outcome of DSAEK, however, seems to be limited, especially in comparison with Descemet membrane endothelial keratoplasty (DMEK). DSAEK cases without graft failure often do not show any definite correlate for the reduced optical performance. In this study, we tried to correlate vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0
2

Year Published

2014
2014
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 17 publications
(29 reference statements)
2
14
0
2
Order By: Relevance
“…Because the cohort was only adequately sampled for the age range of 57 to 75, our findings are best applied to donors of this age group. However, based on the recommendations of others 6,8,23 in the peer-reviewed literature and unpublished data from eye banks, it is likely that most DMEK surgeons share a practice that is similar to ours in the selection of donor age for DMEK surgery. Although this may, in effect, render the sampling bias of this study moot, surgeon preferences in DMEK may still be of continued interest in future studies.…”
Section: Discussionmentioning
confidence: 66%
“…Because the cohort was only adequately sampled for the age range of 57 to 75, our findings are best applied to donors of this age group. However, based on the recommendations of others 6,8,23 in the peer-reviewed literature and unpublished data from eye banks, it is likely that most DMEK surgeons share a practice that is similar to ours in the selection of donor age for DMEK surgery. Although this may, in effect, render the sampling bias of this study moot, surgeon preferences in DMEK may still be of continued interest in future studies.…”
Section: Discussionmentioning
confidence: 66%
“…120 While little is known for certain regarding the role of the graft-host interface in visual performance post-EK, it is thought that interface opacity induces HOAs, loss of contrast sensitivity 140 and loss of acuity. 51 Convergence between the differently orientated host and donor stromal collagen fibres at the interface is considered to be a source of optical aberrations in DSEK / DSAEK -a situation theoretically overcome by DMEK.…”
Section: Influence Of the Graft-host Interfacementioning
confidence: 99%
“…Other authors have shown this to be the cause of nonoptimal visual rehabilitation after surgery. 13 The stroma-stroma interface seen in Descemet stripping endothelial keratoplasty-/DSAEK-operated patients is easily detected upon slit-lamp examination. Suh et al 14 examined failed DSAEK grafts histopathologically to evaluate the etiology of the graft failure, and they too noted fibrocellular proliferation in the DSAEK lenticule-host stroma interface in 58% of cases.…”
Section: Discussionmentioning
confidence: 99%